2021
DOI: 10.1016/j.det.2021.05.016
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines and the Skin

Abstract: : In 2021, we entered a new phase of the COVID-19 pandemic. As mass vaccinations are underway and more vaccines are approved, it is increasingly important for dermatologists to recognize potential cutaneous adverse events. In this article we review the dermatologic manifestations of COVID-19 vaccines worldwide as reported in clinical trial data and summarize additional observational reports of skin reactions to COVID-19 vaccines. Early-onset local injection reactions were the most common cutaneous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 40 publications
2
68
1
5
Order By: Relevance
“…However, similar to SARS-CoV-2 infection, it remains unclear whether there is a real causal relationship between chilblain-like lesions and the vaccine. 8,10,15,28,42 Furthermore, McMahon et al 28 observed a case of mRNA vaccine-induced erythromelalgiaan uncommon condition that has been noted in response to other vaccines as well, such as those for influenza and hepatitis B.…”
Section: Functional Angiopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar to SARS-CoV-2 infection, it remains unclear whether there is a real causal relationship between chilblain-like lesions and the vaccine. 8,10,15,28,42 Furthermore, McMahon et al 28 observed a case of mRNA vaccine-induced erythromelalgiaan uncommon condition that has been noted in response to other vaccines as well, such as those for influenza and hepatitis B.…”
Section: Functional Angiopathiesmentioning
confidence: 99%
“…Notably, these reactions are more commonly observed in individuals younger than 60 years. 8,10,15,42 Type I and type IV hypersensitivity reactions Type I (immediate) Immunoglobulin E-mediated (type I) allergic reactions to antiviral vaccines are usually not caused by the viral antigen but by vaccine ingredients, such as egg proteins, gelatine and formaldehyde. In the case of COVID-19 vaccines, polyethylene glycols (PEGs) and cross-reactive polysorbate 80 have been blamed to be the causal factors for immediate hypersensitive/allergic reactions, such as urticaria, angio-oedema and even anaphylaxis.…”
Section: Early Unspecific Injection-site Reactionsmentioning
confidence: 99%
“…Singular case reports and case series about cutaneous side effects of these agents are available [80,91,92]. A group from the USA has published a comprehensive overview of cutaneous ADRs to various vaccines that deserves mention [93].…”
Section: Granulomatous and Fibrogenic Reactionsmentioning
confidence: 99%
“…On the other hand, most of the adverse skin manifestations expected after vaccination against COVID-19 are mild and are related to the presence of acute signs such as erythema and local edema in the area surrounding the inoculation; these are not usually of clinical concern since they are common to other vaccines, and usually persist for a maximum of three days until their complete resolution without health intervention [61]. The oral cavity can be altered by COVID-19 disease.…”
Section: Vaccinated Without Infectionmentioning
confidence: 99%